Preparing pre-service teachers for practicing sustainable geographies through online technology integration - Cascante Campos, José Alejandro (2023)
The geographic curriculum in Costa Rica’s secondary education follows a sustainability approach aligned to the United Nations sustainable development goals. Students aim to develop a geographic understanding of economic, environmental, and social perspectives of current sustainability challenges at different scales. This vision requires a change on how pre-service teachers must be trained at universities, where sustainability should be addressed by the online integration of technology, pedagogy, and geography when working with students in high schools. On this regard, the present chapter shows the results of a six-week workshop with a group of 28 pre-service teachers, who engaged in the development of a story map, an online geospatial technology for teaching students about food geography and sustainability issues. The results provide opportunities for reflecting on how to prepare future educators for teaching these topics in high schools.